KI in der Schule und Bildungsgerechtigkeit. Blog-Beitrag im fiete.ai-Blog. - Eickelmann, Birgit

Thematic Working Group 8 - Pedagogical Reasoning and Reflective Practice: Teacher's Professional Learning and Development (TLPD) in New Digital Realities - Drossel, Kerstin; Friesen, S.; Phillips, M.; Forkosh, A.; Christensen, R.; Trevisan, O.; Shaffer, D.W.; Horikoshi, I. (Moving forward to new educational realities in the digital era. Report of EDUsummIT 2023)

Zum Ausmaß und Zusammenhang der unterrichtsbezogenen Nutzung digitaler Medien mit der Medienkompetenz von Lehrkräften unter Berücksichtigung von Hintergrundmerkmalen - Caruso, Carina; Drossel, Kerstin; Heldt, M (Lehrerbildung auf dem Prüfstand)

Die Evaluation des Modellschulprojekts ‚Lernen mit digitalen Medien an Förderzentren Geistige Entwicklung/Körperlich-Motorische Entwicklung‘ in Schleswig-Holstein - Gerick, J.; Steglich, E.; Eickelmann, Birgit; Oelkers, J. (Zeitschrift Die Deutsche Schule)

Relevance of Pre-Service Teacher Training to use ICT for the Actual Use in Classrooms – Focus on German Secondary Schools. Technology, Pedagogy and Education - Lorenz, R.; Heldt, M.; Eickelmann, Birgit (Journal for Technology, Pedagogy and Education)

International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) [Datensatz]. Berlin - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

Digitalisierungsbezogene Fortbildung und professionelle Lerngelegenheiten von Lehrpersonen der Sekundarstufe I in Deutschland und im Bundesländervergleich - Eickelmann, Birgit; Lorenz, R.; Endberg, M.; Domke, Marius (Schule digital – der Länderindikator 2021. Lehren und Lernen mit digitalen Medien in der Sekundarstufe I in Deutschland im Bundesländervergleich und im Trend seit 2017)

Children and young people’s narratives and perceptions of ICT in education in selected European countries complemented by perspectives of teachers and further relevant stakeholders in the educational context. (DigiGen- working paper series No.11) - Eickelmann, Birgit; Casamassima, Gianna; Labusch, Amelie; Drossel, Kerstin; Sisask, M.; Teidla-Kunitson, G.; Kazani, A.; Parsanoglou, D.; Symeonaki, M.; Gudmundsdottir, G. B.; Holmarsdottir, H. B.; Mifsud, L.; et al.

Beyond participation: Video workshops across Europe to engage in research with children and young people and teacher candidates as collaborators investigating ICT in education (DigiGen- working paper series No.10) - Casamassima, Gianna; Eickelmann, Birgit; Labusch, Amelie; Drossel, Kerstin; Barbovschi, M.; Gudmundsdottir, G. B.; Holmarsdottir, H. B.; Kazani, A.; Mifsud, L.; Parsanoglou, D.; Sisask, M.; Symeonaki, M.; et al.

International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) [Datensatz] - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

The role of ICT for school leadership and management activities: an international comparison - Tulowitzki, Pierre; Gerick, Julia; Eickelmann, Birgit (International Journal of Educational Management)
Purpose Information and communication technologies (ICT) has an increasing impact on schools. School leaders play a key role in this context as drivers of innovation including those related to ICT. Against this background, the study presented in this article focuses on school leadership and management activities with ICT and related challenges. It sought to analyze how frequently German school principals use ICT compared to principals in other countries, what distinct clusters of German principals could be identified in terms of ICT usage and how principals viewed ICT in schools and related challenges. Design/methodology/approach A mixed-methods approach was chosen, using quantitative data from both the international comparative large-scale assessment study ICILS 2018 and the explorative qualitative data from Germany. For the international comparison, the school principal data sets of the 12 international participants of the International Computer and Information Literacy Study (ICILS) 2018 were taken into account: Chile, Denmark, Finland, France, Germany, Italy, Kazakhstan, Republic of Korea, Luxembourg, Portugal, Uruguay and the United States. To look beyond averaged frequencies, a latent class analysis (LCA) was conducted to identify possible clusters of school leaders with distinct usage patterns of ICT for leadership and management activities. Findings The results indicate that, in general, German principals use ICT for leadership and management activities on a similar level as their international colleagues. However, they seem to communicate with education authorities significantly more often than their international colleagues, whereas representative activities (presentations, home page) are rather infrequent. The qualitative data point to significant barriers to fully harnessing the potential of using ICT for leadership, management and school improvement such as lack of competencies and lack of adequate support. Originality/value To the best of the authors’ knowledge, this is the first study that focuses on school leadership and management activities using ICT with such a data set. The results provide insights into how German principals use ICT to lead and manage their schools compared to their international counterparts. The qualitative data offers additional insights into possible reasons hindering a more effective use of ICT.
Keywords: Organizational Behavior and Human Resource Management; Education; Organizational Behavior and Human Resource Management; Education

Implementierung schulischer Medienkonzepte als Kooperationsanlass - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
In dem Beitrag wird vor dem Hintergrund der Transformationsprozesse der Digitalisierung und der damit einhergehenden Anforderungen an die institutionsübergreifende Zusammenarbeit zwischen Einzelschulen und dem Unterstützungssystem der Kompetenzteams der Medienberatung NRW als exemplarische Form der Kooperation zwischen Einzelschulen und Bildungsadministration analysiert. Entlang des Implementierungsprozesses schulischer Medienkonzepte, welche als zentrale Schulentwicklungsinstrumente für die Umsetzung digitalisierungsbezogener Schulentwicklungsprozesse gelten, wird mithilfe eines längsschnittlichen Fallstudiendesigns und eines Mixed-Methods-Ansatzes den Fragen nachgegangen, welche Gestaltungsformen sich in der Zusammenarbeit zeigen und welche Gelingensbedingungen und Herausforderungen diesem Prozess zugrunde liegen. Der Beitrag fasst die zentralen Untersuchungsergebnisse zusammen und leitet mögliche Implikationen für die Praxis ab.
Keywords: Pharmacology

Computer- und informationsbezogene Kompetenzen und Computational Thinking: Ein Überblick über die Konstrukte der International Computer and Information Literacy Study (ICILS 2018) - Gerick, J.; Eickelmann, Birgit (Kompetenzmodelle für den Digitalen Wandel. Kompetenzmanagement in Organisationen)

Good practice toolkit for improving practice and policies (DigiGen-working paper). - Roth, M. M.; Holmarsdottir, H. B.; Labusch, Amelie; Eickelmann, Birgit; Parsanoglou, D.

Implementierung schulischer Medienkonzepte als Kooperationsanlass. Eine multiperspektivische Betrachtung zu Kooperationsprozessen zwischen Schulen der Sekundarstufe I und dem Unterstützungssystem der Medienberatung NRW - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (MedienPädagogik 49 (Schulentwicklung))

Schule digital – der Länderindikator 2021. Theoretisches Rahmenmodell und Überblick über zentrale Ergebnisse - Lorenz, R.; Eickelmann, Birgit; Endberg, M.; Yotyodying, S. (Schule digital – der Länderindikator 2021. Lehren und Lernen mit digitalen Medien in der Sekundarstufe I in Deutschland im Bundesländervergleich und im Trend seit 2017)

Ziele, Anlage und Durchführung des Länderindikators 2021 - Lorenz, R.; Eickelmann, Birgit; Endberg, M.; Yotyodying, S. (Schule digital – der Länderindikator 2021. Lehren und Lernen mit digitalen Medien in der Sekundarstufe I in Deutschland im Bundesländervergleich und im Trend seit 2017)

Belastungsempfinden von Lehrkräften in der COVID-19-Pandemie-Situation – Empirische Analysen zu Zusammenhängen mit schulischen Input- und Prozessmerkmalen - Drossel, Kerstin; Fröhlich, N.; Gerick, J.; Eickelmann, Birgit (Empirische Pädagogik, 36(2))

Schule digital – der Länderindikator 2021. Lehren und Lernen mit digitalen Medien in der Sekundarstufe I in Deutschland im Bundesländervergleich und im Trend seit 2017